Development of supplier quality performances in a semiconductor company for ISTMET2015 - Zulkifli, Norzima; Abdul Aziz, Faieza; Sivalingam, Sangeethavani (IEEE, 2015)
Supplier quality management (SQM) is considered as a down to business loom in the customers' standpoint to hunt for unremitting supplier quality improvement. Lacking of a proper storage system to monitor Supplier Corrective Action Required (SCAR) leads to limitations of visibilities and also the tracking. Besides that, criterion in justifying a supplier need to be widened from not only limiting to cost and quality but other criterion such as delivery, technology and Green Program also need to be focused. Furthermore, realization towards importance of environment is brought forward through Green Program activity in audit besides unremitting supplier quality improvement. Lacking of a proper storage system to monitor Supplier Corrective Action Required (SCAR) leads to limitations of visibilities and also the tracking. Besides that, criterion in justifying a supplier need to be widened from not only limiting to cost and quality but other criterion such as delivery, technology and Green Program also need to be focused. Furthermore, realization towards importance of environment is brought forward through Green Program activity in audit besides feeding as current market requirement. Therefore, this paper focuses in an effort of developing a system called E-complaint system to create visibilities in SCAR besides supplier rating criterions also have been enhanced to have more criterions to rate the supplier's performances. Nevertheless, improvement in supplier audits was also focused on green program which plays a role in developing the graph bar of supplier's performances. Percentage of improvement is estimated around 30% from the 1st month drop to the improvement on the next month and subsequently increases on the quality of performances and services. The study shows that supplier quality could be managed in many ways and several criteria that have been developed and introduced are contributing in supplier developments.